Longitudinal study of mild delinquency and in-school problem behaviors during junior high school - Obokata, Akiko (Japanese psychological research, 2022)
This research investigates repetitive problem behavior (in-school problems and mild delinquency) in Japanese junior high school students from their first to third year (12-15 years old) and examines the risk factors for repetitive problem behavior among parent-child relationships, school, individual, and lifestyle factors. An analysis of the longitudinal data of 470 students (Data Set 1) found that repeated problem behavior in school was affected by low self-control, poor relationships with teachers, and lack of parental monitoring. Repeated mild delinquent behavior was affected by parental violence, poor relationships with mothers, less sleep duration, and not belonging to club activities. Some students exhibited both mild delinquency and in-school problems. Students who experienced problem behavior 10 times or more in their second year had often experienced some problem behavior (1-9 times) in their first year. Analysis of the longitudinal data of 368 students (Data Set 2) showed that in many cases, students who exhibited repeated delinquent behavior in their second year continued to exhibit problem behavior after they became third-year students. Though the number of students with repetitive mild delinquency that was totally remedied in their third year was small, a low incidence of parental violence was seen as an antecedent factor for students who did not commit mild delinquency in their third year in spite of a high frequency of delinquency in their second year.
Online veröffentlicht: 11. Dezember 2020
Gesehen am 22.11.2023